Screening and partial purification of protease inhibitors from senna surattensis leaves / Ahmad Firdhaus Arham - Arham, Ahmad Firdhaus (2011)
This study was done to determine the inhibitory activity that were exhibited by different parts of the local plants in Malaysia selected from the 4 families which are Leguminosae, Rubiaceae, Apocynaceae and Euphorbiaceae. The screening methods used in this study are Bradford Assay and Trypsin Inhibitory Assay. Both these assays revealed that Senna surattensis leaves showed the highest inhibitory activity of 83 % compared to other 41 plant samples studied in this study. SDS-PAGE and Tricine SDS on this sample extract showed the presence of this protease inhibitor through the formation of band. From these band also, the molecular weight for Senna surattensis leaves was determined to be 27.93 kDa. From the mode of inhibition study carried on Senna surattensis leaves, it was found out that this plant belongs to the competetive inhibitor group with Ki value of 8.89 x10-5 mM. Thermostability test reavealed that Senna surattensis leaves extract can only work best at temperature below 60˚C and achieve its optimum inhibitory temperature at 45⁰C with 87.35 % of inhibitory activity. Senna surattensis leaves extract also showed the ability to inhibit the protein extracted from Chrysomya megacephala through the study performed on the crude Chrysomya megacephala protein extract. The IC50 value of Senna surattensis leaves extract was determined to be 0.0174 μg/μl. Although with all of these promising result, further test need to be done to confirm it.